Regional economic resilience in the European Union: a numerical general equilibrium analysis. Issue 3 (3rd July 2021) - Di Pietro, Filippo; Lecca, Patrizio; Salotti, Simone
ABSTRACT: Using a spatial general equilibrium model, this paper investigates the resilience of European Union regions under three alternative recessionary shocks, each activating different economic adjustments and mechanisms. We measure the vulnerability, resistance and recoverability of regions and identify key regional features affecting the ability of regions to withstand and recover from unexpected external shocks. The analysis reveals that the responses of regions vary according to the nature of the external disturbance and to the pre-shock regional characteristics. Finally, it seems that resilience also depends on factor mobility. The analysis, although designed before the onset of the Covid-19 pandemic, offers interesting insights into how to use a general equilibrium framework to study resilience in such a context.